Sistem Pendeteksi Tempo Lagu Untuk Kontes Robot Seni Tari Indonesia (KRSTI) Berdasarkan Frekuensi Dengan Algoritma Beat This - Tio Haryanto Adi Putra; Dahnial Syauqy; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesian Robot Competitions have become a known competition amongst robotics lover all over the country. Building robots has become its own hobby for the participants generating robots that are though and sophisticated which have a chance to replace human's labor in the future. These sophisticated robots however, are not easily made or built. It requires time and dedications to build one that can complete its purpose. One of the divisions in KRI is KRSTI or Traditional Dance Robot in which robots assumes humanoid figures and must be able to dance along with a given music or song. The process of building one is not easy unfortunately, there are a number of cases in which said robots dance awkwardly or even tipping over against its own weight. Using this research's sensor system, it is hoped that these poor robot will grasp the meaning of beats, loudness and the music's speed or known as tempo. Thus enables them to dance along flawlessly. The testing of said sensor system can give output every 125ms with accuracy up to 95.7%. In addition, this system also give secondary output with accuracy as high as 100% but with delay of two seconds.